2016
DOI: 10.1007/s40195-015-0358-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen on Corrosion and Stress Corrosion Cracking of AZ91 Alloy in Aqueous Solutions

Abstract: The effect of hydrogen on the corrosion and stress corrosion cracking of the magnesium AZ91 alloy has been investigated in aqueous solutions. Hydrogen produced by corrosion in water diffuses into, and reacts with the Mg matrix to form hydride. Some of the hydrogen accumulates at hydride/Mg matrix (or secondary phase) interfaces as a consequence of slow hydride formation and the incompatibility of the hydride with the Mg matrix (or secondary phase), and combines to form molecular hydrogen. This leads to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…The β phase had the ability to capture and accumulate hydrogen and provide a path for crack propagation. [50] Chen et al [51] showed that the aggregation of hydrogen leads to the rupture of the β phase, which was consistent with the results of Winzer et al [22,52] In this study, the rareearth Gd refined the β phase and reduced the volume fraction of the β phase, thus reducing the accumulation of hydrogen in the β phase and inhibiting the rupture of the β phase. Kamilyan et al [53] further demonstrated that the β phase not only promoted the hydrogen embrittlement process but also prevented the dehydrogenation process.…”
Section: Discussionsupporting
confidence: 91%
“…The β phase had the ability to capture and accumulate hydrogen and provide a path for crack propagation. [50] Chen et al [51] showed that the aggregation of hydrogen leads to the rupture of the β phase, which was consistent with the results of Winzer et al [22,52] In this study, the rareearth Gd refined the β phase and reduced the volume fraction of the β phase, thus reducing the accumulation of hydrogen in the β phase and inhibiting the rupture of the β phase. Kamilyan et al [53] further demonstrated that the β phase not only promoted the hydrogen embrittlement process but also prevented the dehydrogenation process.…”
Section: Discussionsupporting
confidence: 91%
“…4 The presence of molecular hydrogen in ZE10A Zr/Nd-rich regions from short-term exposure in water at room temperature is surprising, although internal H 2 has been postulated for Mg alloys after electrochemical charging. 26 In steels, internal H 2 can result from recombination of atomic H that enters the alloy during corrosion and impacts pitting, blistering, and cracking behaviors. 27 Hydrogen from water exposure could conceivably have entered ZE10A as either atomic hydrogen, recombining to H 2 , or directly as molecular H 2 .…”
Section: Hydrogen Speciation Characterization By Insmentioning
confidence: 99%
“…But it is known that the surface of higher atomic density has lower surface energy, and according to the model proposed by Fu et al [36], the surface energy values of (0001), and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) surfaces of Mg alloys are 1.808, 1.868 and 2.156 eV/nm 2 , respectively, which can be transformed into 1.54 9 10 4 , 3.04 9 10 4 and 2.99 9 10 4 J/mol, respectively. According to previous literature, a higher energy surface of metal is beneficial to the adsorption of hydrogen ions and thus promoting the hydrogen evolution reaction [5,37,38].…”
Section: Corrosion Products Characterizationmentioning
confidence: 91%